Inhibitory effects of ginsenosides on basic fibroblast growth factor-induced melanocyte proliferation - Ji Eun Lee; Jong Il Park; Cheol Hwan Myung; Jae Sung Hwang (Journal of Ginseng Research, 2017)
Background: UV-B-exposed keratinocytes secrete various paracrine factors. Among these factors, basic fibroblast growth factor (bFGF) stimulates the proliferation of melanocytes. Ginsenosides, the major active compounds of ginseng, are known to have broad pharmacological effects. In this study, we examined the antiproliferative effects of ginsenosides on bFGF-induced melanocyte proliferation. Methods: We investigated the inhibitory effects of Korean Red Ginseng and ginsenosides from Panax ginseng on bFGF-induced proliferation of melan-a melanocytes. Results: When melan-a melanocytes were treated with UV-B-irradiated SP-1 keratinocytes media, cell proliferation increased. This increased proliferation of melanocytes decreased with a neutralizing anti-bFGF antibody. To elucidate the effects of ginsenosides on melanocyte proliferation induced by bFGF, we tested 15 types of ginsenoside compounds. Among them, Rh3, Rh1, F1, and CK demonstrated antiproliferative effects on bFGF-induced melanocyte proliferation after 72 h of treatment. bFGF stimulated cell proliferation via extracellular signal-regulated kinase (ERK) activation in various cell types. Western blot analysis found bFGF-induced ERK phosphorylation in melan-a. Treatment with Rh3 inhibited bFGF-induced maximum ERK phosphorylation and F1-delayed maximum ERK phosphorylation, whereas Rh1 and CK had no detectable effects. In addition, cotreatment with Rh3 and F1 significantly suppressed bFGF-induced ERK phosphorylation. Western blot analysis found that bFGF increased microphthalmia-associated transcription factor (MITF) protein levels in melan-a. Treatment with Rh3 or F1 had no detectable effects, whereas cotreatment with Rh3 and F1 inhibited bFGF-induced MITF expression levels more strongly than a single treatment. Conclusion: In summary, we found that ginsenosides Rh3 and F1 have a synergistic antiproliferative effect on bFGF-induced melan-a melanocyte proliferation via the inhibition of ERK-mediated upregulation of MITF.